2006
DOI: 10.1016/j.neuron.2006.03.042
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 Contributes to Cold, Mechanical, and Chemical Nociception but Is Not Essential for Hair-Cell Transduction

Abstract: TRPA1, a member of the transient receptor potential (TRP) family of ion channels, is expressed by dorsal root ganglion neurons and by cells of the inner ear, where it has proposed roles in sensing sound, painful cold, and irritating chemicals. To test the in vivo roles of TRPA1, we generated a mouse in which the essential exons required for proper function of the Trpa1 gene were deleted. Knockout mice display behavioral deficits in response to mustard oil, to cold ( approximately 0 degrees C), and to punctate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

58
1,222
8
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,144 publications
(1,290 citation statements)
references
References 50 publications
58
1,222
8
2
Order By: Relevance
“…Bautista et al [41] found that the percentage of cold-sensitive sensory neurons in culture, number of nocifensive responses to acetone-evoked cooling, paw-withdrawal latencies, and induction of shivering in a cold-plate paradigm (20 to −10°C) were indistinguishable in wild type and TRPA1 −/− mice. In the contrary, Kwan et al [85] did report a decrease number of paw lifts when TRPA1 −/− mice were placed upon a surface cooled to 0°C…”
Section: Mouse Models Deficient In Temperature Sensingmentioning
confidence: 90%
See 2 more Smart Citations
“…Bautista et al [41] found that the percentage of cold-sensitive sensory neurons in culture, number of nocifensive responses to acetone-evoked cooling, paw-withdrawal latencies, and induction of shivering in a cold-plate paradigm (20 to −10°C) were indistinguishable in wild type and TRPA1 −/− mice. In the contrary, Kwan et al [85] did report a decrease number of paw lifts when TRPA1 −/− mice were placed upon a surface cooled to 0°C…”
Section: Mouse Models Deficient In Temperature Sensingmentioning
confidence: 90%
“…Working independently, the laboratories of David Julius and David Corey generated TRPA1-null mice and tested their sensitivity to cold [41,85]. In a remarkable similarity to the discrepancies found with TRPA1 responses to cold in vitro, one group observed no cold sensation deficits in the knockout mice, whereas the second group did.…”
Section: Mouse Models Deficient In Temperature Sensingmentioning
confidence: 91%
See 1 more Smart Citation
“…2000) and Dr David Corey (Kwan et al. 2006) and continuously backcrossed to C57BL/6 in our animal facility. The mice were housed in group cages in a temperature‐controlled environment on a 12 h light/dark cycle and were supplied with water and food ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Another notable TRP subunit, TRPA1, gained considerable attention when it was presented as a candidate for the mechanosensitive transduction channel (Corey et al 2004). However, it was later ruled out as a candidate based on the lack of an auditory or vestibular deficit in TRPA1-deficient mice (Bautista et al 2006;Kwan et al 2006). To our surprise, TRPA1 RNA expression spiked over 100-fold in the apex at P0 and P2 relative to the base at P4.…”
Section: Trp Subunits With No or Little Expression And/or No Distinctmentioning
confidence: 99%